Assessment of the efficacy of communication skills training program for oncologists - Bulotienė, Giedrė; Jagelavičiūtė, Gabrielė (Acta medica Lituanica, 2016)
Background. Effective communication is essential for cancer care therefore a communication skills training program was developed by the Lithuanian Association of Psychosocial Oncology. This study aims to identify the efficacy of the new program designed for Lithuanian specialists. Materials and methods. Self-report questionnaires for health care professionals were designed. Surveys were based on three topics – stress, confidence level, and personal opinion about the training and ability to apply learned communication skills. 88(67.2%) respondents completed the questionnaire. Results. Stress: 38.6% of respondents indicated that they usually experience stress while communicating with oncology patients or their relatives; Confidence level: 61.4% of participants agreed that their level of confidence improved after trainings. 83.0% of participants agreed that the  establishment of a  connection with patients and their relatives improved, but requires further development. The  participants’ personal opinion about specific aspects of the communication skills training was evaluated as well. It was found that women are more likely to think that their skill of empathy had developed, but still needed to be improved, while men believed that their empathy had not changed, or stated that it had developed and needed no further improvement (p = 0.003). Conclusions. The  study found improvements in participants’ confidence (61.4%) and specific skills while communicating with oncology patients (75.0–90.9%). Health care professionals evaluated the program as well and very well (86.4–92.1%). The Lithuanian communication skills training program is appropriate to use to enhance the quality of cancer care.
Keywords: oncology; quality of cancer care; communication skills training